The influence of transparency and accountability on taxpayer trust in motor vehicle tax at the Ketintang Samsat, South Surabaya - Maria Diana Suryati Luju; Rudiana Fibriani (Trigin Publisher, 2025)
This study aims to investigate the extent to which tax transparency and public service accountability affect the trust of motor vehicle taxpayers at Samsat Ketintang, South Surabaya. Tax transparency in this study is understood as the level of openness of information related to tax policies, use of tax funds, and administrative procedures that can be easily accessed by the public. Meanwhile, public service accountability is measured based on the agency's ability to provide efficient, responsive, and accountable services. Taxpayer trust is evaluated based on their perceptions of the government's integrity and credibility in managing tax obligations. This study adopts a quantitative approach with a data collection method by distributing questionnaires to 100 motor vehicle taxpayers registered at Samsat Ketintang, South Surabaya. The collected data were analyzed using multiple linear regression to test the effect of each independent variable (tax transparency and public service accountability) on the dependent variable (taxpayer trust). The results of the study show that tax transparency plays an important role in increasing taxpayer trust, by showing that the more open and clear the information regarding tax policies, the higher the level of trust given by taxpayers. In addition, public service accountability also has a significant influence, where the level of fast, accurate, and accountable service further strengthens taxpayer trust in the government. Overall, tax transparency and public service accountability together have a strong impact on increasing taxpayer trust.